HYPERTENSION SCREENING IN MULYOREJO PUBLIC HEALTH CENTER AT 2019: WHAT LESSONS LEARNED? - Shifa Fauziyah; Budi Utomo; Teguh Hari Sucipto (Universitas Airlangga, 2022)
Introduction: Hypertension is one of silent killer that become priority on health coverage era. Early detection and risk factors related must be conduct for effective prevention. Methods: This research aimed to detected earlier hypertension case in adult and elderly people in Mulyorejo Public Health Center (PHC), Surabaya, Indonesia. Survey was conduct from 12th to 19th November with the target adult and elderly that were visited PHC. Structured questionnary were used as a screening instrument, and examination using digital tensimeter were used as gold standard. Family history, smoking, physical activity, vegetable consumption, and fruit consumption were recorded as independent variable. Data were analyzed using chi-square test. Accidental sampling and total 0f 100 participants were joined this research, and 10% of them classified as hypertension based on examination using tensimeter, whereas 16% participants classified as hypertension based on structured questionnaire. Result: Validity was counted, and sensitivity showed 70%, spesifity was 87.78%, positive predictive value was 38.8%, negative predictive value was 96.34%. There’s no significant relationship between the independent variables family history (p=0.48 ; OR=1.64 ; 95% CI= 0.42<OR<6.29), smoking (p=0.21 ; OR=2.96 ; 95% CI= 0.52<OR<16.7), physical activity (p=0.46 ; OR=1.71 ; 95% CI= 0.4<OR<7.29), vegetable consumption (p=0.94 ; OR=0.95 ; 95% CI= 0.25<OR<3.62), fruit consumption (p=0.89 ; OR=1.09 ; 95% CI= 0.29<OR<4.03), salt consumption (p=0.66; OR=1.33; 95% CI= 0.25<OR<6.98). Conclusion: There’s no relationship between independent variables with the hypertension during this study. In case, much effort from health worker to conduct medical check up massively would be needed, so that hypertension not become undetected. Keywords: family history, hypertension, screening, smoking, vegetable consumption